2010
DOI: 10.1103/physrevlett.104.083001
|View full text |Cite
|
Sign up to set email alerts
|

Singular Extremals for the Time-Optimal Control of Dissipative Spin12Particles

Abstract: We consider the time-optimal control by magnetic fields of a spin 1/2 particle in a dissipative environment. This system is used as an illustrative example to show the role of singular extremals in the control of quantum systems. We analyze a simple case where the control law is explicitly determined. We experimentally implement the optimal control using techniques of nuclear magnetic resonance. To our knowledge, this is the first experimental demonstration of singular extremals in quantum systems with bounded… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
180
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 172 publications
(189 citation statements)
references
References 17 publications
3
180
0
Order By: Relevance
“…In this framework, different numerical optimal control algorithms [7][8][9] have been developed and applied to a large variety of quantum systems. Optimal control was used in physical chemistry in order to steer chemical reactions [3], but also for spin systems [10,11] with applications in Nuclear Magnetic Resonance [7,[12][13][14][15][16] and Magnetic Resonance Imaging [17][18][19]. Recently, optimal control has attracted attention in view of applications to quantum information processing, for example as a tool to implement high-fidelity quantum gates in minimum time [4,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, different numerical optimal control algorithms [7][8][9] have been developed and applied to a large variety of quantum systems. Optimal control was used in physical chemistry in order to steer chemical reactions [3], but also for spin systems [10,11] with applications in Nuclear Magnetic Resonance [7,[12][13][14][15][16] and Magnetic Resonance Imaging [17][18][19]. Recently, optimal control has attracted attention in view of applications to quantum information processing, for example as a tool to implement high-fidelity quantum gates in minimum time [4,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Spin baths can be studied by NMR experiments and can be viewed as assemblies of qubits (a qubit is an unit of quantum information in quantum computing). These applications need to study the control of spin baths [14][15][16], but the decoherence processes can drastically decrease the efficiency of the control. Previous studies concerning decoherence of spin baths focused on decoherence induced by spin-spin interactions inner the bath (the spin bath being itself considered as an environment for one of its spins).…”
Section: Introductionmentioning
confidence: 99%
“…In the case γ = 0, this leads to a classical flip of ∆ψ = π(1 − 0.0528). Another option could be to consider the dynamics of a linear chain of three coupled spins subjected to radio-frequency magnetic fields [20,21,22]. Previous studies have shown that the optimal controlled trajectories of this system are given by solutions of Euler equations [23,24].…”
Section: Discussionmentioning
confidence: 99%